Pain assessment in surgical patients in the South Bohemia Region - Olišarová, Věra; Dvořáková, Vendula; Tóthová, Valérie (Ostravská univerzita v Ostravě, Lékařská fakulta, 2020)
Aim: The aim of the study was to describe the current state of pain assessment in surgical patients in the South Bohemia region. Design: A quantitative descriptive study. Methods: Two sets of questionnaires were used to determine the state of pain assessment. The sample included 253 nurses and 205 patients from the South Bohemia region. Results: Nurses use visual analog scales (129) and verbal pain assessment (89) to assess pain. A more precise verbal description of pain assessment would be appreciated by 44 of the respondents, and 42 would appreciate confirmation of assessments by doctors. According to nurses, the main pain manifestations in patients are: limited mobility (156), verbal expressions (134), lack of cooperation (129) and limited independence (128). Direct physical manifestations of pain mentioned by patients include: limited mobility (140), limited independence (97), and mimic manifestation (46). Patients would like pain assessments complemented by more accurate verbal assessments (84), use of pictures to illustrate pain (40), and increased frequency of assessment by doctors (29). Conclusion: The data obtained suggest some shortcomings in pain assessment, and indicate the spheres in which provision of care could be improved.
Hodnocení bolesti u chirurgických pacientů v Jihočeském kraji
Keywords: assessment scales; nurse; pain; pain assessment; surgical patient; hodnotící škály; sestra; bolest; hodnocení bolesti; chirurgický pacient